HISTORICAL STUDY OF THE BRAVERY OF JAT SOLDIERS IN AZAD HIND FAUJ - Mishra, Diwakar; Parveen, Shagufta (ShodhKosh: Journal of Visual and Performing Arts, 2023)
On 4 February 1944, the freedom struggle was fought on the front of Arakan (in Burma, along the border of Manipur), in which Azad Hind Fauj had the upper hand. The British army was pushed back from there. On 18 March 1944, the ’Azad Hind Fauj’ crossed the border for the first time and set foot on Indian soil. Major General Shahnawaz Khan was commanding the No. 1 Division. Later he was also the commander of No. 2 Division. Colonel Gulzara Singh Sikh Jat was commanding the Azad Brigade in this Imphal war. This division of Azad Hind Fauj had surrounded Imphal from all sides. In this siege, a division of the British army was surrounded for more than a month. Colonel Inayat Jan Kayani was the commander of the Gandhi Brigade. This Gandhi Brigade defeated the British army badly.